(untitled) (Eurasian Medical Research Periodical, 2024)
Glaucoma is a leading cause of irreversible blindness worldwide, affecting millions of people, particularly in aging populations. The disease progresses silently, often going undetected until significant vision loss occurs. Early diagnosis and preventive measures are critical to mitigating the impact of this condition. This article explores the importance of early detection and preventive strategies in combating glaucoma, with a focus on awareness campaigns, routine screening programs, advancements in diagnostic technology, and community outreach. It emphasizes the need for integrated healthcare approaches to ensure accessibility to early diagnostic tools and therapies. Drawing upon global practices and case studies, the article outlines a comprehensive strategy for the early diagnosis and prevention of glaucoma, particularly in underserved populations.